Institutionalisation of XBRL in the USA and UK. (12th May 2009) - Abdullah, Aminah; Khadaroo, Iqbal; Shaikh, Junaid
This paper examines the institutionalisation of extensible business reporting language (XBRL) in the USA and UK. It finds that there are variations in the adoption of XBRL, primarily arising from institutional differences and support between the two countries. XBRL seems to have taken deeper root in the USA than the UK primarily because of the relatively stronger institutional 'coercive' pressures. We argue that 'normative' pressures, from the accounting profession, only play a supportive role in the institutionalisation process but do not determine XBRL adoption. Thus, we conclude that mandating XBRL by regulators and obtaining greater support from the accounting profession, software developers and other interest groups are required for the future success of XBRL.